2020
DOI: 10.15408/ajis.v20i1.14704
|View full text |Cite
|
Sign up to set email alerts
|

The Implementation of Shari’a in Aceh: Between the Ideal and Factual Achievements

Abstract: Aceh becomes the only region in Indonesia, where Islamic law is formally implemented. This paper aims at discussing the implementation of shari’a in Aceh, to compare between its ideal and factual achievements. Employing a qualitative socio-legal approach, data is obtained from interviews with the chairperson of Ulama’s Consultative Assembly (Majelis Permusyawaratan Ulama), head of Shari’a Office (Dinas Syariah), scholars, and community leaders. Apart from that, an observation was undertaken to record t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Research by Suma et al found that the execution of law violators strengthened the implementation of Islamic law in Aceh. 67 Likewise, Manan's findings, the application of Islamic law in West Aceh has been going well, although there are still no Islamic behaviours. 68 Thus, Hascall's research question "should qisas be considered a form of restorative justice?"…”
Section: Contextualization Of the Meaning Of Justice In Qisas Lawmentioning
confidence: 92%
“…Research by Suma et al found that the execution of law violators strengthened the implementation of Islamic law in Aceh. 67 Likewise, Manan's findings, the application of Islamic law in West Aceh has been going well, although there are still no Islamic behaviours. 68 Thus, Hascall's research question "should qisas be considered a form of restorative justice?"…”
Section: Contextualization Of the Meaning Of Justice In Qisas Lawmentioning
confidence: 92%
“…This law was enacted at the end of the New Order government's tenure. The law was drafted to gain the sympathy of the Acehnese people and religious leaders, with the goal of quelling the desires for independence, as pursued by separatist groups like GAM (Suma et al, 2020). In general, this law outlines the special status of Aceh and grants special rights to implement Islamic Sharia, which is further elaborated in regional regulations (Article 4, Paragraph 1).…”
Section: Discourse On Islamic Law In Acehmentioning
confidence: 99%
“…11/2006, previously Law No. 44/1999 (Abubakar, 2005;Din & Abubakar, 2021;Suma et al, 2020). Specifically, regarding Law No.…”
Section: Introductionmentioning
confidence: 99%